Desarrollo de una aplicación de comunicación didáctica para fortalecer el lenguaje no verbal basada en software abierto enfocada a niños con discapacidad física-motriz en la “Unidad Educativa Especializada Carlos Garbay” - Mayo Quinaluisa, Jennifer Lisseth (2025)
Nonverbal communication in children with physical and motor disabilities is a vital aspect that helps them express their needs, emotions, and ideas. This enhances their autonomy, reduces frustrations, and facilitates social and academic inclusion. In this context, we present the development of an open-source educational communication platform, a project made possible only through the collaboration of many individuals and organizations. This platform, designed to strengthen nonverbal language, allows for more efficient and fluid communication. The project was carried out in phases using the ADDIE instructional design. The first phase involved analyzing the communication and educational needs and limitations of children with physical and motor disabilities. A web server was then implemented, and a user interface, frontend, and backend were designed using open-source software tools such as Python, HTML, JavaScript, and CSS. A quantitative methodology was adopted to evaluate the system's performance, studying the effect of using the platform on nonverbal communication compared to the traditional method used by tutor teachers in the teaching-learning process of children at the Carlos Garbay Specialized Educational Unit. Finally, after a rigorous statistical analysis, the results indicate that the communication app significantly helped strengthen nonverbal language, with an average of 9 correctly articulated sentences compared to 6 sentences with the traditional method.